"Does your walk match your talk?" Analyzing IPSASs diffusion in developing and developed countries. Issue 2 (19th November 2019) - Polzer, Tobias; Gårseth-Nesbakk, Levi; Adhikari, Pawan
Abstract : Purpose: The purpose of this paper is to provide a global overview of the adoption status of International Public Sector Accounting Standards (IPSASs) in the different contexts of developed and developing countries on central government level, particularly delineating key reform issues and attempts to overcome these. Design/methodology/approach: Drawing on an analytical framework that combines neo-institutional theory with diffusion theory, prior research and official documents were re-analysed. Findings: There are substantial differences regarding whether countries acknowledge having experienced large implementation challenges and the extent to which the reform benefits have been achieved. The study sheds light on the (institutional) underpinnings of these differences. Research limitations/implications: First, the analysis could be extended to regional and local governments, as well as social funds. Both qualitative and quantitative strategies are suggested. Second, the implementation of the conceptual framework deserves further attention. Third, further research should more thoroughly scrutinise cost-benefit analyses used for justifying the (non)implementation of IPSASs, and in particular the assumptions that are being made in such analyses. Practical implications: The paper informs policymakers and standard setters by delineating the areas and issues complicating the widespread adoption of IPSASs across countries, including pointing out directions to overcome these. Social implications: Substantial amounts of public money are invested internationally to converge accounting standards and translate them into native languages. A close(r) monitoring is needed to ensure that these efforts obtain sufficient value for money. Originality/value: This study is original as it applies an analytical framework that combines neo-institutional theory and diffusion theory to examine public sector accounting convergence issues internationally. Such an approach explicitly puts a focus on decoupling between reform "talk" (decision) and "walk" (implementation) and helps to analyse the reasons for this decoupling.